(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2017)
Transcultural studies often theorize third world diaspora from within the dominant Western context, and its relation to the culture of their postcolonial home. This essay takes on a reversed perspective, aiming to examine lmic representations of two young Western subjects in third world countries. The lmmakers Thomas Brück and Bentley Brown spent their formative years as members of Western diaspora families in Mexico and Chad. Using the medium of lm, their work navigates cultures — as the works of certain subaltern immigrant artists and lmmakers in the West do. By analysing their personal documentaries Third Culture Kid and Oustaz, the essay investigates their cinematic means of negotiating transcultural identity across geopolitical borders. Special emphasis is given to the employment of home video material to reconstruct and represent memory.